Landcover and geomorphology influence streamwater temperature sensitivity in salmon bearing watersheds in Southeast Alaska. (18th June 2018) - Winfree, Michael M; Hood, Eran; Stuefer, Svetlana L; Schindler, Daniel E; Cline, Timothy J; Arp, Christopher D; Pyare, Sanjay
Abstract: Climate warming is projected to increase the regional air temperature in Southeast Alaska and alter precipitation patterns and storage, with potentially important implications for the region's aquatic ecosystems. The climate-landcover relationships influencing stream temperature have not been comprehensively evaluated in Southeast Alaskan watersheds, many of which provide spawning and rearing habitat for five species of Pacific salmon. Thus, improving our understanding of current streamwater thermal regimes is critical to assess how stream temperatures across the region may be altered by ongoing climate change. We evaluated seasonal streamwater thermal regimes in forty-seven salmon-spawning watersheds in Southeast Alaska to assess the influence of watershed geomorphic and landscape characteristics on streamwater temperature and sensitivity to variation in air temperature. Stream temperatures were measured during the 2015 water year and analyzed for winter and summer seasons. Mean summer stream temperatures ranged from 4.0 °C–17.2 °C, while mean winter stream temperatures were less variable (0.5 °C–3.5 °C). Maximum weekly average temperatures ranged from 4.3 °C–21.5 °C. Regression and time-series analyses revealed that low gradient watersheds with higher lake coverage experienced warmer summer stream temperatures and were more sensitive to air temperature fluctuations compared to streams draining watersheds with high gradients. Winter mean stream temperatures were warmer in higher gradient watersheds with greater forest and lake coverage. These findings demonstrate that streamwater thermal regimes and sensitivity to air temperature are strongly moderated by watershed geomorphology and landcover, resulting in substantial thermal heterogeneity in streams across the complex terrain characterizing the coastal temperate rainforest of Southeast Alaska.